2021
DOI: 10.1002/rth2.12581
|View full text |Cite
|
Sign up to set email alerts
|

Low ADAMTS‐13 predicts adverse outcomes in hospitalized patients with suspected heparin‐induced thrombocytopenia

Abstract: Background Heparin‐induced thrombocytopenia (HIT) is a life‐threatening thrombotic complication after heparin exposure. However, the role of ADAMTS‐13 and von Willebrand factor (VWF) in the disease process and outcomes of HIT is not known. Objective To determine the potential role of ADAMTS‐13 and VWF in hospitalized patients suspected with HIT. Methods Associations of the HIT tests, ADAMTS‐13 activity, and VWF antigen or activity with other … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 70 publications
1
8
0
Order By: Relevance
“…A positive correlation between PF4 and VWF : Ag levels in type 2A VWD patients (r = 0.229, p = 0.010) was found, which might indicate a similar interaction in vivo (53). Low plasma ADAMTS13 activity or reduced ratio of ADAMTS13 activity to VWF antigen or activity was found prevalent in patients with suspected HIT (54), which suggests that PF4 may reduce VWF cleavage by inhibiting ADAMTS13 activity. Similarly, ADAMTS13 levels were reduced (p = 0.009) and the VWF/ADAMTS13 ratio was increased (p = 0.0004) in convalescent COVID-19 patients with dysregulated angiogenesis and immunothrombosis, while levels of PF4 (a putative protector of VWF) were also elevated (p = 0.0001) (55).…”
Section: Potential Role Of the Pf4-vwf Complex In Immune-associated T...mentioning
confidence: 79%
“…A positive correlation between PF4 and VWF : Ag levels in type 2A VWD patients (r = 0.229, p = 0.010) was found, which might indicate a similar interaction in vivo (53). Low plasma ADAMTS13 activity or reduced ratio of ADAMTS13 activity to VWF antigen or activity was found prevalent in patients with suspected HIT (54), which suggests that PF4 may reduce VWF cleavage by inhibiting ADAMTS13 activity. Similarly, ADAMTS13 levels were reduced (p = 0.009) and the VWF/ADAMTS13 ratio was increased (p = 0.0004) in convalescent COVID-19 patients with dysregulated angiogenesis and immunothrombosis, while levels of PF4 (a putative protector of VWF) were also elevated (p = 0.0001) (55).…”
Section: Potential Role Of the Pf4-vwf Complex In Immune-associated T...mentioning
confidence: 79%
“…VTE is a known complication of surgery that remains as a notable cause of morbidity and mortality. Several studies have found that changes in the ratio of VWF to ADAMTS13 impact thrombosis potential in patients with various diseases [ 49 , 50 , 51 , 52 , 53 ]. The results of this study are consistent with the changes described in the literature and the relationship between VWF, ADAMTS13, and other surgeries [ 20 , 29 , 54 , 55 , 56 , 57 , 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…31,76 The relative deficiency of ADAMTS13 function is a risk factor for the increased mortality rate in these patients. 26,31,[74][75][76][77] Irradiation and/or malignancy may trigger endothelial release of ULVWF and suppress ADAMTS13 synthesis. [78][79][80] Low ADAMTS13 activity and high VWF levels were also shown to be independently associated with an increased mortality rate in patients with malignancy.…”
Section: Discussionmentioning
confidence: 99%
“…The cause of such a moderate deficiency of plasma ADAMTS13 activity is most likely the results of massive release of VWF from vascular endothelium and/or inhibition of ADAMTS13 biosynthesis and release. More recent studies have demonstrated the relative deficiency of plasma ADAMTS13 function (i.e., low ADAMTS13 and high VWF) in hospitalized patients with a suspected heparin‐induced thrombocytopenia 75 and in those with severe/critical COVID‐19, resulting from infection with SARS‐CoV‐2 31,76 . The relative deficiency of ADAMTS13 function is a risk factor for the increased mortality rate in these patients 26,31,74–77 …”
Section: Discussionmentioning
confidence: 99%